2009
DOI: 10.1007/s10899-009-9151-y
|View full text |Cite
|
Sign up to set email alerts
|

Motivators for Resolving or Seeking Help for Gambling Problems: A Review of the Empirical Literature

Abstract: This literature review summarizes recent empirical research on the reasons disordered gamblers try, through treatment or otherwise, to resolve or reduce their gambling problems. Relevant databases and bibliographies were searched for English-language studies, published since 1998, that asked gamblers themselves about motivators for action. Found were ten studies addressing reasons for trying to resolve or reduce gambling problems, five addressing reasons for seeking help and four addressing reasons for request… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
72
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 26 publications
4
72
1
2
Order By: Relevance
“…Compared to the findings of Suurvali et al (2010), the respondents in our study paid relatively more attention to external motives than internal drivers (which included such motives as a sense of guilt arising from the nonfulfilment of social roles and, based on this, decisions about quitting or reducing gambling).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Compared to the findings of Suurvali et al (2010), the respondents in our study paid relatively more attention to external motives than internal drivers (which included such motives as a sense of guilt arising from the nonfulfilment of social roles and, based on this, decisions about quitting or reducing gambling).…”
Section: Discussionmentioning
confidence: 86%
“…Of lesser significance is the impact of gambling venues, legal issues, and problems at work and with living circumstances (Gainsbury et al, 2014). The literature review by Suurvali et al (2010) shows that many of the identified motivators are transnational such as financial problems, relationships with others, negative emotions, the evaluation and decision-making processes about quitting or cutting down on gambling, work or legal difficulties, and that these same motives are recognised in different parts of the world by people with gambling problems.…”
mentioning
confidence: 99%
“…Based in previous empirical research, Gainsbury [4] claimed that VSE programs are under-utilized by problem gamblers. In general, it is known that individuals do not seek help for problem gambling until they reach serious crisis [5].Why do Players "Self-Exclude" and who are they?Reasons for players to self-exclude are manifold. In a study by Hayer and Meyer, [2] players frequently reported excluding as a preventive measure and annoyance with the operator as reasons for VSE.…”
mentioning
confidence: 99%
“…Based in previous empirical research, Gainsbury [4] claimed that VSE programs are under-utilized by problem gamblers. In general, it is known that individuals do not seek help for problem gambling until they reach serious crisis [5].…”
mentioning
confidence: 99%
“…Reasons for declining involvement in gambling include its negative consequences (affecting economy, relationships, and psychological well-being), diminished gambling availability, personal maturation, other priorities in life, and having a more negative attitude towards gambling (Cunningham et al 2009;Suurvali et al 2010). A large percentage of problem gamblers recover from their gambling problems with time, with or without professional help (Abbott et al 2004;Slutske 2006).…”
Section: Introductionmentioning
confidence: 99%